2021
DOI: 10.1097/eja.0000000000001580
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative open-lung ventilatory strategy reduces postoperative complications after laparoscopic colorectal cancer resection

Abstract: BACKGROUND The role of the positive end-expiratory pressure (PEEP) and lung recruitment manoeuvre (LRM) combination (termed open-lung strategy, OLS) during intra-operative mechanical ventilation is not clear. OBJECTIVE To determine whether an open-lung strategy constituting medium PEEP (6–8 cmH 2 O) and repeated LRMs protects against postoperative complications in at-risk patients undergoing laparoscopic colorectal cancer resection under low-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…In the original study, PLOS was a secondary outcome, with no signi cant difference in the per-protocol population between the two groups [12]. In the present study, we reanalyzed the PLOS in all enrolled patients.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In the original study, PLOS was a secondary outcome, with no signi cant difference in the per-protocol population between the two groups [12]. In the present study, we reanalyzed the PLOS in all enrolled patients.…”
Section: Discussionmentioning
confidence: 89%
“…The main results of this trial have been previously published [12]. As a secondary outcome of the trial, the median PLOS did not differ between the two groups [12]. In this secondary analysis of the PROVOLON trial ndings, we aimed to investigate the in uencing factors (especially modi able factors) for PPLOS after laparoscopic colorectal cancer resection.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The use of protective intraoperative mechanical ventilation has been associated with a lower incidence of atelectasis and PPC. Although positive end-expiratory pressure (PEEP) alone can improve intraoperative oxygenation [7], studies have shown that the combination of recruitment maneuvers (RM) and PEEP can improve oxygenation and reduce the incidence of PPCs in patients better than either alone [8][9][10][11][12]. However, when low tidal volumes were used in various ventilator strategies, increasing PEEP with alveolar recruitment maneuvers did not reduce the incidence of postoperative pulmonary complications, as observed in some large studies with large sample sizes [13][14][15].…”
Section: Introductionmentioning
confidence: 99%